2019
DOI: 10.1136/annrheumdis-2019-215862
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-driven selection of antibodies against SSA, SSB and the centromere ‘complex’, including a novel antigen, MIS12 complex, in human salivary glands

Abstract: ObjectivesRecent evidences have revealed that anti-SSA/SSB antibodies, the major autoantibodies in Sjögren's syndrome (SS), are produced in salivary glands. This study aims to clarify overall of autoantibody production at lesion site, including anti-centromere antibody (ACA)-positive SS.MethodsAntibodies of antibody-secreting cells in human salivary glands were produced as recombinant antibodies. The reactivity of these antibodies and their revertants were investigated by ELISA and newly developed antigen-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 38 publications
1
35
1
Order By: Relevance
“…Interestingly, no other differences have been observed among other immunologic parameters including anti-Ro/SSA, RF and cryoglobulins. Anti-La/SSB positivity correlates with more intense inflammatory infiltration of the minor salivary glands, while several reports have shown that ectopic germinal centers within inflamed minor salivary glands are active sites of anti-La/SSB production [ 18 , 19 , 20 ]. In our study, however, there were no differences in salivary gland focus scores between males and females with FS ≥ 1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no other differences have been observed among other immunologic parameters including anti-Ro/SSA, RF and cryoglobulins. Anti-La/SSB positivity correlates with more intense inflammatory infiltration of the minor salivary glands, while several reports have shown that ectopic germinal centers within inflamed minor salivary glands are active sites of anti-La/SSB production [ 18 , 19 , 20 ]. In our study, however, there were no differences in salivary gland focus scores between males and females with FS ≥ 1.…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies against SECD, S1, RBD, and N were measured by antigen-binding bead assays as previously described ( Takeshita et al, 2020 ). In detail, 20 μl of Dynabeads M280 streptavidin (Thermo) were incubated with 4 μg of RBD-SBP, 16 μg of S1-SBP, 32 μg of SECD-SBP, or 10 μg of N-SBP in 100 μl of TBSTx overnight at 4 °C with shaking.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the analyses of a large set of monoclonal antibodies (mAbs), generated from BCR sequences of IgG memory B cells from Sjögren's syndrome or SLE patients, revealed that a substantial proportion was reactive towards extractable nuclear (auto)antigens (ENA) Ro52 and La. However, when reverted to their unmutated ancestor, the ENA antibodies showed polyreactivity with a low, non-specific, binding to Ro52 supporting the idea that SHM contributed to antibody specificity and introduction of autoreactivity [48,49]. Similar phenomena have been described in SLE in studies where two dsDNA-directed autoantibodies did not show self-reactivity anymore when expressed in their germline configuration [43,50].…”
Section: De Novo Autoreactivity Gained Through Somatic Hypermutationmentioning
confidence: 95%